Trait selection and screening of Indonesian local rice accessions for iron stress tolerance (Biodiversitas Journal of Biological Diversity, 2022)
Iron (Fe) poisoning in rice causes changes in both morphological and physiological characteristics of the plants, but the stress response is often genotype-dependent. This research used a screening method on nutrient culture media to evaluate 20 local Indonesian genotypes for tolerance to Fe stress by studying the response of root morphology, vegetative growth, and biomass. This research aimed to identify cultivars that were highly resistant to excess Fe from 20 Indonesian local rice accessions. The research was conducted in a greenhouse from May to June 2019 and used a randomized complete block design with two factors and three replications. The first factor consisted of 20 local Indonesian rice accessions. The second factor was the concentration of Fe in the nutrient media (0, 100, 200, and 300 ppm Fe). The results showed that the high Fe concentration in the nutrient solution decreased root growth, vegetative growth, and biomass in a genotype-specific manner. The application of > 200 ppm Fe in the medium resulted in inhibition of plant growth characterized by yellowing and dry leaves, a decrease in the number of root branches, root length, number of tillers, leaf length, and shoot/root biomass. Several tolerant cultivars were discovered, including Inpara 9, Lipigo 2, and Sigambiri Merah, which could be useful in tolerance breeding. Evaluation of all parameters identified shoot dry weight and number of leaves as reliable traits to assess Fe toxicity tolerance in rice.